Related donor platelet transfusion improves platelet transfusion refractoriness in hematological patients - Zhang, Jing-Cheng; Ni, Li-Hong; Tu, Yan; Hu, Hui-Xian (Frontiers in Medicine, 2023)
Objective Transfusion of HLA-matched platelets can reduce the effect of alloimmune responses on platelet transfusion efficacy; however, finding HLA-matched platelets in the population is nearly impossible. Almost all HLA-matched platelets from related are half-matched, but the hemostatic efficacy of related donor platelets is unclear. Our goal was to compare the hemostatic effect of related donated platelets and unrelated donors platelets. Methods In this retrospective cohort study, we included acute leukemia and myelodysplastic syndrome patients with thrombocytopenia after chemotherapy. These patients were all transfused with platelets. This study excluded patients younger than 16 years and older than 65 years, or patients with abnormal coagulation parameters during platelet transfusion. We compared the hemostatic effect of related donated platelets and unrelated donors platelet. The primary outcome was transfusion efficacy after platelet transfusion, and the number of platelet counts and corrected count increments at 24 h after platelet transfusion. Result We analyzed 31 patients who received platelet transfusions from related donors (Treatment group) and 35 patients who received platelet transfusions from unrelated donors (Comparator group). Except for the relatively small proportion of patients with myelodysplastic syndrome in the treatment group, baseline clinical and laboratory characteristics were similar between the two groups. Hemostasis and prevention of bleeding in the treatment group showed significant superiority; the number of platelets increased 24 h after platelet transfusion in the treatment group was significantly higher than that in the comparator group. After 24 h, the corrected count increments treatment group was also higher than the comparator group; in the treatment group, the transfusion effect was better when the three sites of HLA-A, B, and C were identical, and the different blood types of platelet donors and recipients did not affect the transfusion effect. Conclusion Related donated platelets have better hemostasis and prevention effects, and no increase in adverse blood transfusion reactions. It may be a better transfusion strategy for platelet refractoriness patients in emergency situations.